Capacity of surface water to reduce air multi-pollution in urbanized areas (the City of Krakow, southern Poland) - Pierri, Dorota; Myszkowska, Dorota; Casado, Alba; Mitana, Paulina (Geology, Geophysics and Environment, 2024)
The study analyzes changes in the physico-chemical parameters in a 400 cm2 artificial water reservoir with distilled water, exposed to a 2-week (±2 days) period of atmospheric conditions in Krakow. After nearly 500 days, dry and wet deposition caused a shift from neutral to acidic pH levels (7.30–5.12, averaging 6.22 pH) and an average electric conductivity of 19.5 μS/cm (1.6–143.0 μS/cm). The study investigated chemical and biological pollutants, including pollen and fungal spores. Three distinct air quality periods were identified: (1) characterized by vehicle and combustion-related pollutants (Oct-Jan), (2) a transitional phase with increased biological particles (Feb-May), and (3) dominated by pollen and fungal spores (Jun-Sep). Despite peak air pollution in the warmest months, air temperature showed an inverse relationship with pollutant concentration, possibly due to decreased air humidity. Precipitation positively impacted air quality. The artificial reservoir received a total of 0.7 kg of air pollutants  (723.6 mg/m2 of surface water table). This corresponds to an annual load of 0.5 kg (551.4 mg) and a daily load of 1.51 mg. The reservoir’s pollutant capture capacity was estimated at 28% ±21% (mean±SD), with a critical value of 12%. The study evaluated Krakow’s surface water reservoirs’ capacity to mitigate air pollution, indicating potential benefits for urban air quality.